Ultrasonography in the diagnosis of lumbar disc herniation in young adult - Abdullaeiv, Rizvan; Mamedov, Ilgar (ScienceRise: Medical Science, 2022)
The aim: to assess the value of ultrasonography in the diagnosis of a lumbar herniation disc in young adults. Material and methods: 27 patients aged 17-21 years (8 girls, 19 boys) were included in our study. During the examination by a neurologist, all patients reported pain in the lower back. The results of the ultrasound investigation were compared with MRI. Ultrasonography (USG) was conducted on a Philips HD 11XE device using a convection transducer in the frequency range 2-5 MHz; MRI - General Electric, Signa HDI, 1.5T. Results: at the L3-L4 segment, hernia was diagnosed in 2 (7.4±5.0 %) cases, at the L4-L5 segment - in 14 (51.9±9.6 %) cases, and at the L5-S1 segment - in 11 (40.7±9.5 %) cases, respectively. The hernia at the segments of L5-S1 and L4-L5 was diagnosed significantly (P<0.001) more often than at the segment of L3-L4. Median hernia was diagnosed in 12 (44.4±9.6 %) cases, paramedian - in 11 (40.7±9.5 %) cases and posterolateral - in 4 ( 14.8±6.8 %) cases, respectively. The median and paramedian hernia was diagnosed significantly (P<0.05) more than the posterolateral. In ultrasound, only in one case, a posterolateral hernia was interpreted as paramedian Conclusions: 1) The lumbar hernia are localized at the segments of L5-S1 and L4-L5 significantly (P<0.001) more often than at the other segments; 2) Sciatica is significantly more common in posterolateral localization of lumbar disc herniation; 3) The ultrasonography couldbe used to find out the causes of back pain in young adult